Safeguards for the independent functioning of public service media providers. The legal position of domestic legislation that is not in compliance with Article 5 EMFA - Enrico Albanesi (Rivista Italiana di Informatica e Diritto)
The aim of this article is to comment on Article 5 of the European Media Freedom Act (EMFA), about safeguards for the independent functioning of public service media providers, and shaping the legal position of domestic legislation in this field, which will not be in compliance with that article from the date (8 August 2025) when Article 5 EMFA begins to apply.